Requests for termination of pregnancy in the East Midlands area - Seager, C. P. (1974)
A study was carried out of patients seeking termination of pregnancy through their general practitioners. Three quarters of these patients were recommended for termination. Of these 80 per cent did, ultimately, have the pregnancy aborted. A number of patients showed guilt feelings but anything approaching mental illness occurred in only two patients.